Recent Trends in the Nucleophilic [18F]-radiolabeling Method with No-carrier-added [18F]fluoride - Kim, Dong Wook; Jeong, Hwan-Jeong; Lim, Seok Tae; Sohn, Myung-Hee (Nuclear medicine and molecular imaging, 2010)
Noninvasive imaging in living subjects with positron emission tomography (PET) provides early detection of diseases in humans. For this application, it is necessary to prepare specific molecular imaging probes labeled with positron-emitting radioisotopes such as fluorine-18 for obtaining high-quality PET imaging. In this review, we describe recent trends in the F-18 radiolabeling method for the introduction of no-carrier-added fluorine-18, which was obtained from an 18 O(p,n) 18 F reaction, into a specific molecular site, which in turn is intended to serve as an imaging agent for PET study. These labeling protocols are based on ionic liquid media 18 F radiofluorination in the presence of some water, enzymatic 18 F fluorination using fluorinase in water solution, non-polar protic alcohol media 18 F radiofluorination and its mechanism, and nucleophilic 18 F fluorination of an aromatic iodonium salt precursor.